How do government environmental concerns affect haze pollution? - Lv, Yanqin; Fan, Tianzheng; Zhao, Bin; Zhang, Jinning; Zheng, Ying; Zhang, Ziye (Frontiers in Environmental Science, 2022)
The air pollution problem, represented by the frequent occurrence of haze, has seriously affected the quality of China's economic growth. Along with the in-depth implementation of the concept of sustainable development and the continued strengthening of the central government's environmental accountability, local governments' environmental concerns have also increased. So, do local government environmental concerns have an impact on haze pollution? Based on theoretical analysis, this paper uses text analysis and machine learning to construct local government environmental concern indicators, and selects a panel of 284 cities in China from 2007 to 2020 for research. The study shows that local government environmental concerns effectively reduce haze pollution, and the conclusion still holds after considering robustness. Local government environmental concerns can force cities to improve green innovation and industrial structure optimization, alleviating haze pollution. There are heterogeneous effects of local government environmental concerns on haze pollution under different regions, different resource endowments, different central assessment systems and different changes of government officials; the double difference results show that, in addition to local government environmental concerns, central government environmental concerns can also reduce haze pollution. Based on the above findings, the central government should further improve the officials' appraisal system and give play to the government's active role in environmental governance.